Requirement of Strong Legal Framework and Procedures to Contest with Cybercrime in Pandemic Situation: Dr. Aftab Ahmad Malik, Dr. Mujtaba Asad, Dr. Waqar Azeem - Dr Aftab Ahmad Malik; Mujtaba Asad; Dr Waqar Azeem (International Journal for Electronic Crime Investigation, 2021)
One of the most significant global occurrences in recent history will be the COVID-19 pandemic in 2020. The government's response to issuing legal stay-at-home orders is one facet of this situation that is unique. COVID-19 has affected the world in several ways not seen in decades. One of the effects is crime rates, which appear to have fallen in some communities around the world. We argue that the government's order to stay at home may be the principal reason for the change. While in some other countries, there has been an increase. In fact, the impact has been different in different ways. The important question is how the effect on the rate of crime will be in the future; increase or reduction. The tendency of crime regarding torturing, abusing, molesting, assaulting, raping, or killing innocent women and children increased. Pakistan formulated fresh legislation. The major role in combating the crime depends upon the existence of strong legislation capable of causing a reduction in the crime rate, which allows the investigators vast powers and collaboration with the prosecution and safeguarding the witnesses. The criminals are very well organized and use the most modern technology and IT equipment, therefore, the police, investigators, and prosecutors must have and be highly trained and equipped, similarly. No strategy can be successful in the absence of strong legislation. The criminals involved in Cybercrime and white-collar crime keep on acquiring and hacking the data of people, government, and business organizations by crossing security barriers of computers and networks. The occurrence of crime increased particularly in threats to attack and asking for money to stop the attack. More strict security measures must be adopted to safeguard the data and networks and strong encryption attained and implemented. The European Union advocates focusing on a strong legal framework. In addition, there exist justifications to amend the US cyber legal framework to reduce the frequency of crime. The paper presents some salient legal, procedural, and feasible measures. The most salient philosophy presented in this research paper is that there must exist strong legislation coupled with morality, a code of ethics, and severe punishment as deterrent forces to combat these offenses.